A study on Consumer Perception towards GST with reference to Bengaluru City. - R, MANJULA. (South Eastern European Journal of Public Health, 2024)
The Goods and Services Tax (GST) was imposed in India with the main goal of lightening the burden on all economic stakeholders. Consumer are crucial stakeholders in the GST since they indirectly pay taxes and make a donation to the government funds. preceding introduction the GST, there were numerous levies in place, which resulted in greater taxation of taxpayers was complicated, and there was a difficulty with increasing taxes. GST was introduced as a solution to the problems. of prior tax regimes and offer numerous advantages to consumers